1995
DOI: 10.1111/j.1439-0523.1995.tb00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between electrophoretic pattern of storage proteins and gluten strength in durum wheat landraces from Turkey

Abstract: A collection of 180 Triticum durum lines from Turkey and 22 Italian cultivars were investigated by eiectrophoretic techniques and evaluated for grain parameters such as protein content and sodium dodecyl sulphate (SDS)-sedimentation test. A total of 14 different patterns were observed for high-molecular-weight (HMW) glutenin subunits resulting from the combination of three alleles from the A genome and seven from the B genome. Three new allelic variants, one at Glu-A 1 and two at Glu-Bl, were found. Five diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
4
15
3
Order By: Relevance
“…At Glu-B1, the most frequent alleles were d (6+8) and e (20x+20y) in agreement with Brites et al (1996), Igrejas et al (1999) and Raciti et al (2003). Other studies have shown negative effects of Glu-B1e on quality Turchetta et al, 1995;Brites and Carrillo, 2001). At Glu-A3, alleles a and e were the most frequent in our collection, while b and h were more widespread in germplasm from other Mediterranean countries (Igrejas et al, 1999;Moragues et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…At Glu-B1, the most frequent alleles were d (6+8) and e (20x+20y) in agreement with Brites et al (1996), Igrejas et al (1999) and Raciti et al (2003). Other studies have shown negative effects of Glu-B1e on quality Turchetta et al, 1995;Brites and Carrillo, 2001). At Glu-A3, alleles a and e were the most frequent in our collection, while b and h were more widespread in germplasm from other Mediterranean countries (Igrejas et al, 1999;Moragues et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
“…turgidum in our germplasm (Table 2). Several studies Turchetta et al, 1995;Brites and Carrillo, 2001) have shown the better quality associated with the presence of an encoded subunit at this locus. At Glu-B1, the most frequent alleles were d (6+8) and e (20x+20y) in agreement with Brites et al (1996), Igrejas et al (1999) and Raciti et al (2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This diversity is substantially greater than reported by previous studies conducted in durum wheat (Turchetta et al 1995;Cherdouh et al 2005;Moragues et al 2006c). The considerable variability of glutenin combinations found in LR can potentially enhance their value in breeding to broaden the genetic basis of gluten quality improvement, beyond what can be achieved by using modern germplasm.…”
Section: Discussioncontrasting
confidence: 47%